2010
DOI: 10.1111/j.1365-2745.2009.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological differences between genetic lineages facilitate the invasion of non‐native Phragmites australis in North American Atlantic coast wetlands

Abstract: Summary1. Over the last century, native Phragmites australis lineages have been almost completely replaced along the North American Atlantic coast by an aggressive lineage originating from Eurasia. Understanding the mechanisms that facilitate biological invasions is critical to better understand what makes an invasive species successful. 2. Our objective was to determine what makes the introduced lineage so successful in the study area by specifically investigating if morphological and ecophysiological differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 49 publications
9
119
2
Order By: Relevance
“…elevated CO 2 and N) regardless of genotype. Based on this experiment and previous work showing that introduced Phragmites has traits that support relatively high productivity in field settings (Mozdzer and Zieman 2010;Mozdzer and Megonigal 2012;Tulbure et al 2012), we suggest that the spread of introduced Phragmites will increase CH 4 emissions from North American wetlands, and that methane emissions will increase as atmospheric CO 2 concentration continues to rise. These changes in CH 4 emissions will cause radiative forcing unless there is an equivalent increase in carbon sequestration (Poffenbarger et al 2011).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…elevated CO 2 and N) regardless of genotype. Based on this experiment and previous work showing that introduced Phragmites has traits that support relatively high productivity in field settings (Mozdzer and Zieman 2010;Mozdzer and Megonigal 2012;Tulbure et al 2012), we suggest that the spread of introduced Phragmites will increase CH 4 emissions from North American wetlands, and that methane emissions will increase as atmospheric CO 2 concentration continues to rise. These changes in CH 4 emissions will cause radiative forcing unless there is an equivalent increase in carbon sequestration (Poffenbarger et al 2011).…”
Section: Discussionmentioning
confidence: 57%
“…We previously demonstrated greater growth and productivity in the introduced lineage under ambient field conditions (Mozdzer and Zieman 2010) and under predicted global change conditions (Mozdzer and Megonigal 2012). As a consequence of greater growth in an elevated CO 2 environment, we hypothesized an increase in CH 4 emissions proportional to plant growth.…”
Section: Introductionmentioning
confidence: 96%
“…Introduced P. australis shoots emerge earlier in the growing season, produce double the total and leaf biomass, and transition faster from buds to root or shoot tissues (League et al, 2006). Compared with the native lineage, introduced P. australis has a 38 -83% larger photosynthetic canopy, higher specific leaf area, and maintains a 51% greater photosynthetic rate (Mozdzer and Zieman, 2010). Patches of introduced P. australis are also denser and taller than the native lineage.…”
Section: Native Vs Introduced Phragmites Australismentioning
confidence: 99%
“…Recent studies highlighting differences between the native and introduced types of Phragmites indicate that the shift from the native to the introduced lineage may have important ecosystem consequences. For example, the introduced types has been shown to have greater aboveground biomass (League et al 2006, Saltonstall and Stevenson 2007, Mozdzer and Zieman 2010, greater stem density (League et al 2006, Mozdzer andZieman 2010), greater height (League et al 2006), and greater photosynthetic rates (Mozdzer and Zieman 2010). However, the question still remains as to what makes the introduced Eurasian lineage so successful in invading North American tidal marshes.…”
Section: Introductionmentioning
confidence: 99%
“…Since pre-industrial times, anthropogenic N inputs have doubled along the North American Atlantic coast (Galloway et al 2004), and at the same time, introduced Phragmites has outcompeted the native type (Saltonstall 2002), and has expanded into historically unoccupied habitats throughout North American wetlands (Chambers et al 1999). Correlative studies have suggested that increased N availability is a factor facilitating the introduced Phragmites invasion (Bertness et al 2002, King et al 2007, and this shift in N availability is necessary for the invasion since the introduced lineage demands approximately four times more N than the native type in mid-Atlantic tidal marshes (Mozdzer and Zieman 2010). This suggests that there is a threshold of N beyond where the introduced Phragmites has an advantage in the field.…”
Section: Differences Between Native (F) and Introduced (M) Phragmitesmentioning
confidence: 99%